Pendampingan Pembuatan Nomor Induk Berusaha (NIB) melalui Online Single Submission (OSS) bagi UMKM di Desa Wai Muli Timur Lampung Selatan - Zukryandry; Andra Vidyarini; Firdawati; Ailsa Azalia; Annisa Fitri (Civitas Consecratio: Journal of Community Service and Empowerment, 2025)
One of the prerequisites for micro and small businesses (MSMEs) to obtain business legality is the Business Identification Number (NIB), which also gives them access to a number of government benefits, including funding, government training programmes, participation in certified training, government procurement contracts, and more. Nevertheless, many MSMEs in the Wai Muli Timur region lack an NIB. This is mostly due to three factors: small business owners' ignorance of the significance of having an NIB, their lack of familiarity with the online single submission system, and their inadequate comprehension of the procedure for getting legal documents. A multidisciplinary group of instructors and students from Politeknik Negeri Lampung developed an integrated help strategy in response to these difficulties. A number of tactics were used, such as mapping MSMEs to identify their legal requirements, NIB socialisation, OSS system training, helping with data entry at the village office, and making door-to-door visits to business owners who were having trouble with digital literacy or internet access. Each strategy—socialization to fill in knowledge gaps, training to enhance comprehension, and proactive outreach to remove access barriers—was created to specifically address the underlying issues. Twenty business owners received their NIBs as a consequence of these efforts, and fifteen more are in the process of finishing their paperwork. With the help given, information and digital literacy problems that had previously impeded business owners were successfully resolved. In addition to increasing the number of MSMEs with NIBs, this programme made a big difference by increasing business owners' knowledge of legal compliance, facilitating better access to financing programmes like KUR, boosting their confidence in enrolling in government-provided training programmes, and producing MSME data for the village administration. Positive answers from MSME participants show that the cooperative strategy involving academics, students, and village leaders is successful in resolving the technical and structural issues the community faces. In addition to enhancing enterprises' legal standing, this programme fortifies the village's ecosystem for economic empowerment. When it comes to applying for NIBs and other legal documents, this collaboration-based help model can be duplicated in other regions with comparable issues, especially in villages with little information, internet access, and digital literacy.